2011
DOI: 10.1002/cncr.25833
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of LAPTM4B polymorphisms with cervical carcinoma

Abstract: BACKGROUND: Lysosome-associated protein transmembrane 4 beta (LAPTM4B), a novel oncoprotein, is overexpressed in several carcinomas. Previous studies revealed that LAPTM4B polymorphisms contribute to the risk of certain types of cancers. The purpose of this study was to investigate the association between different LAPTM4B alleles and the risk of cervical carcinoma. METHODS: A case-control analysis was performed in 317 patients with cervical cancer and 416 control subjects. Genomic DNA was extracted from perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Thirteen of the 17 eligible studies were HB studies and the remaining four were PB studies. The studies focused on the following cancer types: four liver cancer [15-18]; two lung cancer [19,20]; two breast cancer [21,22]; one cervical carcinoma [23]; one colon, rectal, and oesophageal cancers [24]; one gallbladder carcinoma [25]; one gastric cancer [26]; one nasopharyngeal carcinoma [27]; one ovarian cancer [28]; one pancreatic cancer [29]; one lymphoma [30]; and one endometrial carcinoma [31]. All of the patients were confirmed by histopathologic examination.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the 17 eligible studies were HB studies and the remaining four were PB studies. The studies focused on the following cancer types: four liver cancer [15-18]; two lung cancer [19,20]; two breast cancer [21,22]; one cervical carcinoma [23]; one colon, rectal, and oesophageal cancers [24]; one gallbladder carcinoma [25]; one gastric cancer [26]; one nasopharyngeal carcinoma [27]; one ovarian cancer [28]; one pancreatic cancer [29]; one lymphoma [30]; and one endometrial carcinoma [31]. All of the patients were confirmed by histopathologic examination.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that LAPTM4B polymorphism was associated with susceptibility to liver cancer, 26,33 gall bladder carcinoma 26 cervical carcinoma, 34 gastric cancer, 27 breast cancer, 24,25 colon cancer, 28 endometrial carcinoma, 20 and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that LAPTM4B *2 allele was associated with increased susceptibility of lung cancer [20], gastric cancer [21], colorectal cancers [22], lymphoma [26], cervical cancer [23] and breast cancer [24]. The risk of developing these cancers were increased to 1.720, 1.710, 1.512, 1.610, 1.490, and 1.301 fold in individuals carrying allele *2 in comparison with *1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Allele*1 differs from allele*2 in that it contains only one copy of a 19-bp sequence in the first exon, whereas this sequence is duplicated and tandemly arranged in allele*2 (Figure 1). Previous studies showed that the LAPTM4B *2/2-type allele was significantly associated with the susceptibility of adenocarcinoma including lung cancer [20], gastric cancer [21], colorectal cancers [22], cervical cancer [23] and breast cancer [24], but not in squamous cell carcinoma such as esophageal carcinoma, rectum carcinoma [22], and nasopharyngeal carcinoma[25]. However, the origin of melanocytes is unique: derived from the neural crest cells.…”
Section: Introductionmentioning
confidence: 99%